Silencing of long non-coding RNA linc01106 suppresses non-small cell lung cancer proliferation, migration and invasion by regulating microRNA-765. Issue 1 (31st December 2022) - Zhang, ZuXiong; Li, WeiZhi; Jiang, DaMei; Gu, Liang; Li, Bin; Sang, ChengPeng; Rao, DingYu; Tang, ZhiXian; Liu, Chi
Abstract : Long non-coding RNAs (lncRNAs) are actively involved in various carcinomas. The purpose of this experiment is to explore the function of long intergenic non-protein coding RNA 01106 (LINC01106) in non-small cell lung cancer (NSCLC). LINC01106 expression in NSCLC was determined by RT-qPCR. Next, the distribution of LINC01106 in A549 cells was observed using subcellular fractionation. Subsequently, functional assays were performed to access NSCLC cell biological behaviors, with epithelial–mesenchymal transition detected by the western blot analysis. After that xenograft tumors were established in nude mice to analyze the inhibitory role of LINC01106 knockdown in NSCLC. In addition, gain-of-function and loss-of-function assays were carried out to confirm the interaction between LINC01106 and microRNA (miR)-765 and between miR-765 and collagen type III (COL3A1) in NSCLC cells. LINC01106 was overexpressed in NSCLC cells, and it existed in both cytoplasm and nuclei in A549 cells. Then, it was further discovered that LINC01106 knockdown greatly reduced NSCLC cell expansion and tumor growth in vivo. Furthermore, it was identified that LINC01106 could serve as a sponge of miR-765 to promote COL3A1 expression. miR-765 overexpression inhibited A549 cell activities. This study unmasked that LINC01106 knockdown suppressed NSCLC progression by serving as a sponge of miR-765 to downregulate COL3A1 expression.